Discrimination and favouritism among South African workers: Ethnic identity and union membership. (November 2019) - Ravetti, Chiara; Sarr, Mare; Munene, Daniel; Swanson, Tim
Highlights: We use a lab-in-the-field experiment to study ethnic and labour discrimination between coal mineworkers in South Africa. In repeated dictator games, we distinguish discrimination and favouritism compared to an uninformed baseline behaviour. We find that trade union identity encourages broad altruism towards workers, while ethnic affiliation does the opposite. The ethnic majority (Zulu) discriminates against minority groups and even against co-ethnics (although to a smaller extent). Subcontracted workers from the ethnic majority, with less stable jobs and lower wages, drive this discriminatory behaviour. Abstract: This paper analyses the ways in which ethnic identity and labour institutions shape favouritism and discrimination among workers. We conduct a lab experiment in the field with South African coal miners from various ethnic groups and with different trade union membership status. Our analysis suggests that union identity and ethnic identity are two social constructs that operate in a distinct and opposite fashion. Unionization acts as a factor of workers solidarity beyond the confine of union membership. Conversely, ethnicity operates as the linchpin through which discrimination among workers is infused not only between ethnic majority and minorities, but also within the majority group itself. We find that the widespread practice of subcontracting in the mining sector exacerbates ethnic discrimination among workers both between and within ethnic groupings.